Artificial Intelligence in practice (International Journal of Scientific Research and Management (IJSRM), 2023)
There are three papers written by me in the context of artificial intelligence [1][2][3]. This paper does not develop a novel concept as in three papers but relies on the concept that the machine language or the language of computer is 0 and 1.[4]